SOLUTION FOCUSED THERAPY UNTUK MEMPERBAIKI KOMUNIKASI PADA PASANGAN SUAMI ISTRI - Hardiyanti Rahmah (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2020)
In marital relationships, communication is the main thing to note, because so many problems in the family arise due to misunderstandings when communicating. This study aims to correct communication problems that are intertwined between family members that often cause misunderstandings, because of the openness of each family member in communicating. This study uses the qualitative method that is a case study. The subjects in this study were married couples who had conflicts due to direct communication. Measurement of data used to diagnose family problems, namely, interview, observation and primary communication inventory (PCI). The intervention given to the subject is by providing solution-focused therapy. The results of this study showed a good change, namely communication in the family becomes more open between husband and wife. Keywords: Solution-focused therapy, communication, husband and wife.